Government and not-for-profit accounting. Conceptys and practices - GRANOF, Michael H (John Wiley & Sons, 2004)
Revised and updated, Granof’s Third Edition incorporates the latest GASB pronouncements and takes a fresh look at the unique features of governmental and not-for-profit accounting. This text will help you develop a firm grasp of the theory underlying current practice, so you can quickly acquire the skills required of professional accountants and auditors. Throughout, the emphasis is on the significance of reported information and how to interpret and analyze accounting information.